Pengaruh Kompensasi dan Lingkungan Kerja terhadap Kinerja Pegawai di Universitas Muslim Indonesia - Suprianto Suprianto (Jurnal Manajemen Riset Inovasi, 2023)
The Importance of Employee Performance in Company Development and the Role of Human Resources in Achieving Goals at the Universitas Muslim Indonesia. Various factors affect employee performance, such as education, training, a conducive work environment, motivation, and appropriate compensation. This article explains how providing appropriate compensation can influence work performance, motivation, and job satisfaction, as well as how an adequate work environment can improve employee performance. In conclusion, this article states that employee performance is a crucial factor in the success of a company, and companies must pay attention to employee needs to achieve organizational goals. The importance of human resources in improving company performance is also highlighted. The key factor in achieving success at the Universitas Muslim Indonesia is through the potential and performance of each employee. Companies can improve employee performance by providing education, training, and appropriate compensation and creating a conducive work environment and motivation. Compensation is part of the reciprocal relationship between the company and human resources. The work environment also plays a vital role in enhancing employee performance. Therefore, the company must provide an adequate work environment, both physically and psychologically, to improve employee performance.